Student Management in Character Building at SD Muhammadiyyah Plus Semarang - Kirana Rahmadita; Abdul Wahid (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Rapid social and technological developments have an impact on the behavior of students in elementary school, including the emergence of individualism tendencies, declining academic honesty, and weakening social awareness. This condition shows that character training is not enough to be done through normative learning, but requires planned, systematic, and sustainable management of students. This research aims to examine in depth the management of students in the formation of honest character and social care in SD Muhammadiyah Plus Semarang. The main issue of this research is that the internalization of the values of honesty and social care in the real behavior of students has not been optimal, even though these values have been integrated into the curriculum and school culture. This research uses a qualitative approach with a case study type. The subjects of the study include school principals, classroom teachers, Islamic Religious Education teachers, and parents of students. Data collection techniques were carried out through in-depth interviews, observations, and documentation, while data analysis used Miles and Huberman's interactive model with triangulation of sources and time to maintain the validity of the data. The focus of the research is directed at planning, implementation, the role of teachers and the school environment, as well as the mechanism for monitoring and evaluating student character. The results of the study show that the management of students at SD Muhammadiyah Plus Semarang is carried out in an integrated manner through planning based on the values of honesty and social concern, daily habits such as character control books, cooperative learning, Friday infaq programs, and teacher examples. The school environment and parental involvement also strengthen the internalization of character values, so that students not only understand the value of honesty and social concern cognitively, but also feel them affectively and train them in daily life. This study concludes that consciously and consistently designed student management plays an important role in shaping honest and socially caring characters in elementary school students. Therefore, it is recommended that schools strengthen the synergy between student management planning, teacher examples, and parental involvement, as well as develop reflective and sustainable evaluation characters to ensure that character values are fully internalized in students. Keywords: Student Character, Honesty, Social Care